USING TWO STAYS TWO STRAY (TSTS) TECHNIQUE TO INCREASE STUDENTS’ SPEAKING SKILL - Bahrudin, Dinar Vincy Yunitaka (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Speaking is one of the important elements in communication. In order to make a good communication, speaker must have delivered clear information to receiver. The mastery of speaking skills in English is a priority for many foreign language learners such as in Indonesia. Teacher must be creative in using a good method or innovation technique to make the students interest to study English especially in speaking. Two Stay Two Stray is a cooperative learning technique that promotes better learning, improve student motivation, and increases enjoyment of the learning experience. The aim of the research is to know the using of Two Stay Two Stray technique in improve the students’ speaking ability and to know what are the students’ increases toward Two Stay Two Stray technique in teaching speaking. The research design is Classroom Action Research which consist of two cycles. The implementation of action research consists of planning, acting/implementing, observing and reflecting. In collecting the data, several instruments are used: observation, test and documentation. The analyzed data was the result of the students in every test and the result of observation conducted. From the result, test in cycle I and test in cycle II was getting improvement, in pre-test mean score was 25%, after that the researcher used Two Stay Two Stray as technique in teaching speaking, in the cycle I the students score of test doesn’t improve 65%. So that, the researcher continued to the next cycle and the result of cycle II was successful, the students’ score in test was improve 90%. So that, the used of Two Stay Two Stray brings a positive impact to the students’ speaking skill.